Ein cloze test zur sprachstanderhebung portugiesischer L2 lerner des deutschen - Setas, Clara (2022)
This study aims to test the feasibility of a research tool, a Cloze Test, developed to assess the proficiency of German as a second language (L2) in native speakers of European Portuguese (EP). The Cloze Test is a fill-in-the-gap test used as a tool to measure the participants’ proficiency of linguistic competence, taking into account their lexical, morphosyntactic and discursive knowledge of varying complexity levels. The research conducted presents a Cloze Test in German that was tested on a group of 37 adult native Portuguese speakers who have acquired German as L2 (mainly in a classroom environment). The results of this study indicate that this type of instrument allows to assess language proficiency as it presents a clear complexity hierarchy, with the potential to identify the different proficiency levels of the participants. Moreover, statistical correlations between test scores, self-assessments and extralinguistic input factors show that test scores correlate with both self-assessment and the type of L2 contact. The results are further discussed concerning the role of various input variables. The article ends with a discussion of some limitations of this study, while also highlighting future research to be conducted in this field